Towards greener environment: Energy efficient pathways for the transportation sector in Malaysia - Indati M.S.; Ghate A.T.; Leong Y.P. (Institute of Physics Publishing, 2023)
Transportation sector is the second most energy consuming sector after industrial sector, accounting for 40% of total energy consumption in Malaysia. The transportation sector is one of the most energy intensive sectors in the country and relies primarily on petroleum products, which in total account for nearly 98% of the total consumption in the sector. Since it is heavily reliant on petroleum based fuels, the sector contributes significantly to the greenhouse gas (GHG) emissions. The need to reduce the greenhouse gas emission is paramount as Malaysia at Conference of the Parties (COP15) pledged to reduce its carbon intensity by 40% by 2020 from 2005 level subject to availability of technology and finance. Transport sector will be among the first sectors that need to be addressed to achieve this goal, as two-thirds of the emissions come from fuel combustion in transport sector. This paper will analyse the factors influencing the transport sector's growth and energy consumption trends and discuss the key issues and challenges for greener environment and sustainable transportation in Malaysia. The paper will also discuss the policy and strategic options aimed towards energy efficient pathways in Malaysia. Published under licence by IOP Publishing Ltd.